Controlled Drug Release from Ureasil-Polyether Hybrid Materials - Santilli, Celso Valentim [UNESP]; Chiavacci, L. A. [UNESP]; Lopes, L. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Oliveira, Anselmo Gomes de [UNESP] (Amer Chemical Soc, 2009)
Flexible, transparent, and insoluble urea-cross-linked polyether-siloxane hybrids presenting a tunable drug delivery pattern were prepared using the sol-gel method from PEO (poly(ethylene oxide)) and PPO (poly(propylene oxide)) functionalized at both chain ends with triethoxysilane. Different polyether chain lengths were used to control the urea/siloxane (named ureasil) node density, flexibility, and swellability of the hybrid network. We herein demonstrate that the drug release from swellable hydrophilic ureasil-PEO hybrids can be sustained for some days, whereas that from the unswellable ureasil-PPO hybrids can be sustained for some weeks. This outstanding feature conjugated with the biomedically safe formulation of the ureasil cross-linked polyether-siloxane hybrid widens their scope of application to include the domain of soft and implantable drug delivery devices.